Lavender Essential Oil as an Adjuvant Therapy for Anti-Depression - Brylyani, Diyani Shafira; Algristian, Hafid (Yayasan Sinergi Kawula Muda, 2025)
This study aims to examine the potential of lavender essential oil as an adjuvant therapy for anti-depression by analyzing its effects on mental well-being. The method used is a systematic literature review, focusing on clinical and experimental studies that investigate the impact of lavender essential oil on depressive symptoms. The literature review explores its pharmacological properties, including its influence on neurotransmitters and stress-related biomarkers. The results indicate that lavender essential oil demonstrates anxiolytic and antidepressant effects, potentially enhancing conventional treatments. However, further clinical trials are needed to establish standardized dosages and mechanisms.